Protective effects of Devosia sp. ANSB714 on growth performance, immunity function, antioxidant capacity and tissue residues in growing-finishing pigs fed with deoxynivalenol contaminated diets. (November 2018) - Li, Xiaoying; Guo, Yongpeng; Zhao, Lihong; Fan, Yu; Ji, Cheng; Zhang, Jianyun; Ma, Qiugang
Abstract: This study aimed to investigate the toxic effects of deoxynivalenol (DON) and the effectiveness of Devosia sp. ANSB714 for alleviation of DON toxicosis in growing-finishing pigs. A total of twenty pigs were allocated equally to four treatments for 18 days: CON (basal diet formulated with normal rice), Devosia sp. ANSB714 (CON + Devosia sp. ANSB714), DON (toxic diet formulated with DON-contaminated rice), and DON + Devosia sp. ANSB714. The treatments of Devosia sp. ANSB714 and DON + Devosia sp. ANSB714 were given the fermentation liquor of Devosia sp ANSB714 by drinking water. DON-contaminated diet significantly decreased the average daily gain of growing-finishing pigs. Serum IgA content was significantly increased in DON treatment compared with that in CON. Besides, DON in diet also significantly reduced the activities of GSH-Px in the liver and serum of pigs. Supplementation of Devosia sp. ANSB714 in drinking water effectively prevented these adverse effects of DON on pigs. Moreover, the DON residues in the serum, liver and kidney were significantly decreased with the addition of Devosia sp. ANSB714 to diet contaminated with DON. Taken together, it is effective to feeding Devosia sp. ANSB714 to pigs fed with diet contaminated with DON and ameliorating DON toxicosis of pigs. Highlights: This study investigated the toxic effects of deoxynivalenol (DON) in growing-finishing pigs. Studied the efficiency of Devosia sp. ANSB714 in counteracting DON-induced negative effects of growing-finishing pigs. Devosia sp. ANSB714 alleviated the toxicity of DON toxicosis in growing-finishing pigs. Devosia sp. ANSB714 decreased DON residues in tissues of growing-finishing pigs.